The Role of MicroRNAs in Aβ Deposition and Tau Phosphorylation in Alzheimer’s Disease - Zhao, Juanjuan; Yue, Dongxu; Zhou, Ya; Jia, Li; Wang, Hairong; Guo, Mengmeng; Xu, Hualin; Chen, Chao; Zhang, Jidong; Xu, Lin (Frontiers in Neurology, 2017)
Alzheimer’s disease (AD), with main clinical features of progressive impairment in cognitive and behavioral functions, is the most common degenerative disease of the central nervous system. Recent evidence showed that microRNAs (miRNAs) played important roles in the pathological progression of AD. In this article, we reviewed the promising role of miRNAs in both Aβ deposition and Tau phosphorylation, two key pathological characters in the pathological progression of AD, which might be helpful for the understanding of pathogenesis and the development of new strategies of clinical diagnosis and treatment of AD.